2004
DOI: 10.1111/j.0014-3820.2004.tb00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Molecular Evolution in Nuclear Genes of East Mediterranean Scorpions

Abstract: Scorpions of the genus Mesobuthus represent a useful terrestrial model system for studying molecular evolution. They are distributed on several Aegean islands and the adjacent mainland, they are believed to have low rates of dispersal, and evolutionary divergence dates of taxa are available based on biogeographic events that separated islands from each other and the mainland. Here, we present data on polymorphism and synonymous (Ks) and non-synonymous (Ka) substitution rates for nine nuclear protein-coding gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
4
28
1
Order By: Relevance
“…The estimate T div was calculated with the formula T div  = TΘ/(2μ). Here Θ and T, the scaled divergence specify Θ and T (time), were estimated with MDIV; a μ value of ∼1% divergence per million years for scorpion mtDNA COI was obtained from rate estimates from the Mediterranean Mesobuthus scorpion genus as it represents a robust rate estimate for this mitochondrial gene [29], [64].…”
Section: Methodsmentioning
confidence: 99%
“…The estimate T div was calculated with the formula T div  = TΘ/(2μ). Here Θ and T, the scaled divergence specify Θ and T (time), were estimated with MDIV; a μ value of ∼1% divergence per million years for scorpion mtDNA COI was obtained from rate estimates from the Mediterranean Mesobuthus scorpion genus as it represents a robust rate estimate for this mitochondrial gene [29], [64].…”
Section: Methodsmentioning
confidence: 99%
“…Buthus scorpions are widely distributed over large parts of Africa and show a circum-Mediterranean stronghold including the Mediterranean islands, with extraordinarily high diversity in North Africa [10]–[14]. Yet, molecular studies showed that diversity may still be underestimated and additional cryptic species may be abundant [14]. Most buthid scorpions are strictly territorial and philopatric and have low dispersal abilities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the other discussions about endemism of some snake species occurring in the two island origin of Cyprus (Troodos and Kyrenia island); Hierophis cypriensis , in only southern Cyprus (i.e., Throodos island) while Platyceps najadum (non-endemic)and Natrix tessellata (non-endemic) is distributed only in northern Cyprus (i.e., Kyrenia island) and also on the mainland (Göçmen et al 2009). Gantenbein and Keightley (2004) stated his analyses shows that Mesobuthus cyprius occurring in Cyprus is autochthonous. Mesobuthus cyprius recorded in both southern and northern Cyprus.…”
Section: Resultsmentioning
confidence: 99%
“…According to widely accepted theory is Mediterranean salinity crisis that the Mediterranean sea dried out and these two island or the Trodos island and southern Tauruian-Kyrenian peninsula connected via landbridges about 5.6 Myrs (Hsü et al 1977; Cavazza and Wezel 2003). When the refilling of the Mediterranean basin, Cyprus terrestrial animals was isolated for around 5.2 – 5.3 Myrs (Robertson 1998; Gantenbein and Keightley 2004 ). This isolation played a major role in forming actual scorpion fauna of Cyprus and molecular and morphological phylogenetic analysis has revealed that populations of the island of Cyprus represent a divergent lineage; so these have been assigned to the species rank (i.e., Mesobuthus cyprius Gantenbein and Kropf, 2000).…”
Section: Resultsmentioning
confidence: 99%